Evaluasi User Experience Pada Website Progate.Com Menggunakan Indikator UX Honeycomb - Andikarama Prasida; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In the era of technological advancement, more and more people are looking for knowledge through internet networks, which one is e-learning. E-learning is increasingly being accessed not only by students but among college students and workers, who also need e-learning. The progate.com website is one of the e-learning tools to learn the world of programming, where the website provides various types of programming languages. But the progate.com website itself has weaknesses based on complaints from user experience. Therefore, the progate.com website will be evaluated. The purpose of this evaluation is not only to find out what level of user experience of the progate.com website are, but also to be taken into consideration for the future development of the Progate.com website. This evaluation uses the UX Honeycomb indicator as a basis for measuring the level of user experience from the progate.com website. Respondents of this study were divided into three categories, namely users aged <19 years, 19-23 years, and >23 years, where each category contained 30 respondents. So for the total respondents there are 90 people. In collecting data, this study uses a questionnaire distribution method. The data from the questionnaire will be processed using descriptive statistics. The results of data processing show that the valueable element has a good category because it has an average of 77%. Usable element has a good category because it has an average of 75%. And for the useful element itself, it has the most satisfying value with the very good category because it has an average of 85%.